Experimental Analysis of the Effect of ISOFIX Child Restraint System’s Harness Tension on Child Occupant’s Chest Acceleration in Frontal Collisions - Wei, Zhe (UI Scholars Hub, 2022)
The research seeks to ascertain the relation between ISOFIX child restraint system’s harness tension and child occupant’s chest acceleration in frontal collisions, and analyze the potential risks posed by different harness tensile forces. It is important to verify and validate the effects of harness tensions on child occupants’ potential injuries, since child restraint system’s user manual does not indicate the extent to which the adjusting belt should be pulled generally, thus making it possible to cause the harness tensile force to be applied arbitrarily. Hence, public awareness of the issue should be improved. A test scheme was devised and conducted to collect necessary information about P1.5 dummy in frontal collisions. The pulling forces applied to the adjusting belts were set at 3 different levels. Chest accelerations were acquired and compared to analyze the effects. Based on test results, the relation was ascertained and validated. Additionally, suggestions were made about adjusting the harness tension and appropriate use of ISOFIX child restraint system.